Pengaruh Leverage, Ukuran Perusahaan, Pertumbuhan Perusahaan, Profitabilitas dan Struktur Modal terhadap Manajemen Laba: Studi Empiris pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Muhammad Nur; Slamet Mudjijah (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
Earnings management is the intervention by management in the process of determining the company's earnings to gain benefits from external parties. This study aims to provide empirical evidence regarding the influence of leverage, company size, company growth, profitability, and capital structure on earnings management in the Food and Beverage Subsector companies for the period 2019-2023. The sampling technique used in this study is purposive sampling, resulting in a sample of 12 companies. The results of this study indicate that leverage, profitability, and capital structure have a significant impact on earnings management, while company size and company growth does not have a significant effect on earnings management.